TVDI estimate to assess water conditions in sugarcane production areas in the Brazilian semiarid region. - Martins, Caick M. R. [UNESP]; Lopes, Pabrício Marcos Oliveira; Martins, Antonio Cesar Germano [UNESP] (Revista Brasileira de Geografia Fisica, 2022)
Sugarcane is one of the most important agricultural crops for the Brazilian market. Monitoring its water demand is essential for proper management, and from this, it is possible to evaluate and measure the morphophysiological development of plants, following their growth throughout the cycle. There are several biophysical parameters that estimate the water conditions of the crop, including the Temperature Vegetation Dryness Index – TVDI. The objective of this work was used TVDI to evaluate water conditions in sugarcane production areas in Brazil semiarid through the relationship of biophysical parameters using geoprocessing and remote sensing techniques. The highest average of 0.64 TVDI was found on the dates 2014/09/22 and 2016/08/10 both with 64.0% of dry area. The lowest TVDI average, 0.41, occurred on 2013/30/05. Elevated TVDI is related to the initial stages and after harvest, periods when the soil is most exposed to high global radiation and dryness. The lowest values of TVDI were found in the advanced development stages when the crop showed high density, covering the soil and decreasing the level of dryness. TVDI proved to be able to characterize the complexity of the dryness of the surface conditioned to the different differences and levels of sugar cane biomass that covered the soil, helping in the irrigation management, leading to more effective and accurate actions.
Estimativa do TVDI para avaliação das condições hídricas em áreas de produção de cana-de-açúcar no semiárido brasileiro.
Keywords: dryness; geotechnology; irrigation; triangle method